PERAN MADRASAH DINIYAH DALAM MEMBINA AKHLAK SANTRI MELALUI PROGRAM BIMBINGAN DAN KONSELING SPIRITUAL - Al Matin Nia Yukhafi; Wahyudi Setiawan; Azid Syukroni (TARBAWI:Journal on Islamic Education, 2022)
As a religious being, moral development that includes spiritual-religious, and social aspects must be balanced. In this case, Madrasah Diniyah Awaliyah At-Taubah, Gading Village, Trenggalek as an Islamic Education Institution is very concerned about this aspect as evidenced by the existence of a spiritual guidance and counseling program that is used in fostering the morals of its students. This study aims to determine how the moral development, the results and factors supporting and inhibiting the moral development of students through spiritual guidance and counseling programs. This research is a type of descriptive qualitative research with a case study approach, in which data is collected through interviews, observation, and documentation. The research shows that moral development through spiritual guidance and counseling programs is carried out in the form of classical and group services which results in success in its development marked by significant changes in the character of students. In addition, there are supporting factors, namely the enthusiasm of students to take part in a series of lessons, the consistency of the madrasa in running the program, the availability of infrastructure, family support in moral development, and community awareness to meet the needs of religious education for children. While the inhibiting factor is the family where some parents have busy hours, as a result children become less supervised.